Body Mass Index and Decline of Cognitive Function. - Sujin Kim; Yongjoo Kim; Sang Min Park (PLoS ONE, 2016)
BACKGROUND:The association between body mass index (BMI) and cognitive function is a public health issue. This study investigated the relationship between obesity and cognitive impairment which was assessed by the Korean version of the Mini-mental state examination (K-MMSE) among mid- and old-aged people in South Korea. METHODS:A cohort of 5,125 adults, age 45 or older with normal cognitive function (K-MMSE≥24) at baseline (2006), was derived from the Korean Longitudinal Study of Aging (KLoSA) 2006~2012. The association between baseline BMI and risk of cognitive impairment was assessed using multiple logistic regression models. We also assessed baseline BMI and change of cognitive function over the 6-year follow-up using multiple linear regressions. RESULTS:During the follow-up, 358 cases of severe cognitive impairment were identified. Those with baseline BMI≥25 kg/m2 than normal-weight (18.5≤BMI<23 kg/m2) were marginally less likely to experience the development of severe cognitive impairment (adjusted odds ratio [aOR] = 0.73, 95% CI = 0.52 to 1.03; Ptrend = 0.03). This relationship was stronger among female (aOR = 0.63, 95% CI = 0.40 to 1.00; Ptrend = 0.01) and participants with low-normal K-MMSE score (MMSE: 24-26) at baseline (aOR = 0.59, 95% CI = 0.35 to 0.98; Ptrend<0.01). In addition, a slower decline of cognitive function was observed in obese individuals than those with normal weight, especially among women and those with low-normal K-MMSE score at baseline. CONCLUSION:In this nationally representative study, we found that obesity was associated with lower risk of cognitive decline among mid- and old-age population.